The Retail Industry's Organizational Culture: A Special Reference to Bangalore City - Dr. Veena Ishwarappa Bhavikatti; Apoorva M P; Meenakshi V (Journal of Social Responsibility, Tourism and Hospitality, 2024)
This study looks at Bangalore's retail industry's organizational culture. By means of an extensive examination of business procedures, employee relationships, and leadership approaches, the study seeks to identify the fundamental components influencing the culture of the firm. The study's insights might help to clarify the distinctive cultural environment of Bangalore's retail industry, providing insightful viewpoints for both scholars and enterprises. The research on organizational culture within the retail sector in Bangalore reveals the internal environment and influences their performance, employee engagement, and overall success. In the backdrop of the bustling city of Bangalore, renowned for its vibrant economy and diverse workforce, this research examines the multi-dimensional facets of organizational culture that shape the behavior, values, and interactions of retail businesses.